Definition of long-bone nonunion: A scoping review of prospective clinical trials to evaluate current practice. Issue 11 (November 2021) - Wittauer, Matthias; Burch, Marc-Antoine; McNally, Martin; Vandendriessche, Thomas; Clauss, Martin; Della Rocca, Gregory J.; Giannoudis, Peter V.; Metsemakers, Willem-Jan; Morgenstern, Mario
Highlights: Nonunions are common complications after long-bone fracture, however the related definition remains controversial and varies widely. The aim of this literature review was to identify the definitions and diagnostic criteria used to describe nonunion after long-bone fractures. In the current orthopaedic literature, there is a lack of consensus with regard to the definition of long-bone nonunion. Without valid and reliable definition criteria for nonunion, standardization of diagnostic and treatment algorithms remains problematic. The lack of a clear definition emphasizes the need for a consensus-based approach centred on clinical, radiographic and time-related criteria. Abstract: Aim: Although nonunions are among the most common complications after long-bone fracture fixation, the definition of fracture nonunion remains controversial and varies widely. The aim of this study was to identify the definitions and diagnostic criteria used in the scientific literature to describe nonunions after long-bone fractures. Methods: A comprehensive literature search was performed in PubMed, Cochrane Library, Web of Science, and Embase. Prospective clinical studies, in which adult long-bone fracture nonunions were investigated as main subject, were included in this analysis. Data on nonunion definitions described in each study were extracted and collected in a database. Results: Although 148 studies met the inclusion criteria, only 50% (74/148) provided a definition for their main study subject. Nonunion was defined in these studies based on time-related criteria in 85% (63/74), on radiographic criteria in 62% (46/74), and on clinical criteria in 45% (33/74). A combination of clinical, radiographic and time-related criteria for definition was found in 38% (28/74). The time interval between fracture and the time point when authors defined an unhealed fracture as a nonunion showed considerable heterogeneity, ranging from three to twelve months. Conclusion: In the current orthopaedic literature, we found a lack of consensus with regard to the definition of long-bone nonunions. Without valid and reliable definition criteria for nonunion, standardization of diagnostic and treatment algorithms as well as the comparison of clinical studies remains problematic. The lack of a clear definition emphasizes the need for a consensus-based approach to the diagnosis of fracture nonunion centred on clinical, radiographical and time-related criteria.